Funcionamiento familiar y estrategias de afrontamiento en adolescentes del Centro Poblado El Milagro distrito de Huanchaco - Santa Cruz Espinoza, Henry (2019)
Adolescence is considered a critical period, it is at this stage where there is some vulnerability to different situations. Both family functionality and coping strategies have played an important role in healthy development, as well as being indicators of well-being, especially at this stage of the life cycle. Despite this, their relationship has not yet been elucidated. Based on this context, this study of cross-correlational and comparative design pursues the purpose of the relationship of family functioning and coping strategies in adolescents in the center of Huanchaco district. A sample of 441 adolescents between 11 and 18 years was evaluated. To obtain the information, you can consult the Scale of Cohesion and Family Adaptability FACES IV of Olson, Gorall and Tiesel, and the Coping Scale for Adolescents ACS, of Frydenberg and Lewis. We conclude the evidence of medium-sized relationships, between some dimensions of family functionality and coping strategies in the male sex. In women, the relationship between family overinvolvement and the strategy focuses on the positive; and between the family communication and the strategy fixed in the positive. Most adolescents, men and women, perceive their family functioning as unbalanced and only small differences are found, by sex in each of its dimensions. Similarly, small differences are seen in coping strategies between men and women.